Eine neue Realität im Kundenservice: Ist es aus Marketing-Sicht sinnvoll, Kundenservices auf Augmented Reality-Technologie aufzubauen? - Jessica Hartwig; Florian Botzenhardt; Hans-Michael Ferdinand (Markenbrand, 2016)
– Since the 1960s, people dream to enrich the reality with virtual elements. Today, technologies like Smartphones are widely available and grant easy access to Augmented Reality services. This article examines the usefulness of Augmented Reality as a tool for customer services that go beyond funny filters on Snapchat. Literature Review clearly shows that Augmented Reality can be seen as a service itself. But when it comes to professional usage scenarios, it is the quality that matters. An analysis based on the service value concept shows that within Augmented Reality lies a huge potential for customer services that grant benefits to both the customer as also the service-providing company. Finally, a study shows that there is more acceptance for augmented-reality-driven services among digital natives than among digital immigrants.
Keywords: 650